PENGARUH KETIDAKPASTIAN LINGKUNGAN DAN DESENTRALISASI TERHADAP KINERJA MANAJERIAL DENGAN KARAKTERISTIK SISTEM INFORMASI AKUNTANSI MANAJEMEN SEBAGAI VARIABEL INTERVENING (Studi Empiris pada Industri Rumah Sakit di Jawa Tengah) - Setya Utami, Pramita Diah; Hadiprajitno, Basuki (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to examine the indirect relationship between contextual factors (perceived environmental uncertainty and decentralization) and managerial performance through management accounting system as an intervening variable within hospital industry. The study population was a hospital industry in Central Java. Data collected by sending questionnaires to the manager and assistant manager of the hospital, the amount sent as many as 150 questionnaires. Total return and can be used as many as 45 questionnaires (30%). Testing data using multiple regression extended with the path analysis. The results of this study indicate that the positive effect of uncertainty management accounting system. Decentralization positive influence on management accounting system. Management accounting system does not affect managerial performance. Environmental uncertainty and decentralization had no effect on managerial performance through the use of management accounting systems. It can be concluded that of the five hypotheses only hypothesis 1 and 2 are acceptable while the other hypotheses are rejected.